PENGARUH DEBT TO ASSET RATIO, RETURN ON ASSET DAN TOTAL ASSET TURN OVER TERHADAP PERTUMBUHAN LABA PADA PT. SINAR MAS MULTIARTHA TBK PERIODE 2011-2022 - Ridwan, Dede; Priyanto , Aria Aji (Journal of Research and Publication Innovation, 2024)
This research aims to prove whether or not there is an influence of Debt to Asset Ratio (DAR), Return on Assets (ROA), and Total Asset Turnover (TATO) on Profit Growth at PT. Sinar Mas Multiartha Tbk. The method used in this research is associative quantitative with the data technique used is secondary data. The data analysis techniques used are descriptive statistics, classical assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests, multiple linear regression, hypothesis testing using partial t-tests, simultaneous F tests and coefficient of determination. By using Statistics Product Service And Solution (SPSS) software version 25. The results of this study show that Debt to Asset Ratio partially has a significant effect on profit growth, Return on Assets partially has a significant effect on profit growth and Total Asset Turnover partially has no significant effect. on profit growth and simultaneously Debt to Asset Ratio, Return on Assets, Total Asset Turnover have a significant effect on profit growth.